The Effectiveness of Groin Modifications to Reduce the Impacts of Indian Ocean Dipole (IOD)-induced Port Siltation in Adapting to Climate Change - Romdani, Andhy; Amanulloh, Fahmi Rahmat; Mudatsir; El Ghifari, Muhammad Raka; Gusnadi, Zakwan; Putri, Tryantini Sundi; Empung; Al-Huseiny, Mohammad Syarif (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2025)
Climate anomalies significantly affect coastal hydrodynamics, influencing sediment transport processes. The interaction between waves and currents plays an important role in sediment transport, which is closely related to climate anomalies, particularly the Indian Ocean Dipole (IOD). Indonesia is currently facing severe threats from port siltation due to the impacts of climate change. Port siltation results from sediment transport and can reduce the effectiveness and safety of port activities. This study aims to investigate sediment transport processes at Titan Coal Port under the influence of the IOD in 2016 and 2019. This port is located on the western coast of Sumatera, where high waves from the Indian Ocean pose a risk. Groins and a breakwater have been installed to protect the port from littoral drift induced by southeastern longshore currents and waves. However, the study found that during the negative IOD in 2016, hydrodynamic conditions led to shallowing of the port basin and navigation channel due to longshore currents from the northeast. The methods used in this research include descriptive analysis (using ERA-5 data from the Copernicus Climate Change Service) and numerical modeling (using MIKE 21) with bed level change identification at several points after groin modification scenarios. The combination of tidal currents and waves primarily shaped current patterns in the study area. High-speed currents caused significant erosion upstream at the bed level of the port basin. However, modified groin installations effectively reduced flow velocity entering the port basin. Two modified groin installation scenarios were tested in the study area to alter existing coastal hydrodynamics and sediment transport patterns.